Cymensifin A: a promising pharmaceutical candidate to defeat lung cancer via cellular reactive oxygen species-mediated apoptosis - Bruno Cesar Costa Soares; Bruno Cesar Costa Soares; Hnin Ei Ei Khine; Boonchoo Sritularak; Boonchoo Sritularak; Pithi Chanvorachote; Pithi Chanvorachote; Rosa Alduina; Rungroch Sungthong; Chatchai Chaotham; Chatchai Chaotham (Frontiers Media S.A., 2024)
Background: The upgrade of natural products for cancer treatment is essential since current anticancer drugs still pose severe side effects. Cymensifin A (Cym A) isolated from an orchid Cymbidium ensifolium has shown its potential to induce the death of several cancer cells; however, its underlying molecular mechanisms are hitherto unknown.Methods: Here, we conducted a set of in vitro preliminary tests to assess the cytotoxic effects of Cym A on non-small-cell lung cancer (NSCLC) cells (A549, H23, H292, and H460). A flow cytometry system and Western blot analyses were employed to unveil molecular mechanisms underlying cancer cell apoptosis caused by Cym A.Results: Cym A at 25-50 μM caused the death of all NSCLC cells tested, and its cytotoxicity was comparable to cisplatin, a currently used anticancer drug. The compound induced apoptosis of all NSCLC cells in a dose-dependent manner (5-50 μM), proven by flow cytometry, but H460 cells showed more resistance compared to other cells tested. Cym A-treated H460 cells demonstrated increased reactive oxygen species (ROS) and downregulated antioxidants (catalase, superoxide dismutase, and thioredoxin). The compound also upregulated the tumor suppressor P53 and the pro-apoptotic protein BAX but downregulated pro-survival proteins (BCL-2 and MCL-1) and deactivated survival signals (AKT and ERK) in H460 cells. Cym A was proven to trigger cellular ROS formation, but P53 and BAX were 2-fold more activated by Cym A compared to those treated with hydrogen peroxide. Our findings also supported that Cym A exerted its roles in the downregulation of nuclear factor erythroid 2-related factor 2 (a regulator of cellular antioxidant activity) and the increased levels of cleaved poly (ADP-ribose) polymerase (PARP) and cleaved caspase 3/7 during apoptosis.Conclusion: We propose that Cym A induces lung cancer cell death via ROS-mediated apoptosis, while the modulation of cellular ROS/antioxidant activity, the upregulation of P53 and BAX, the downregulation or deactivation of BCL-2, MCL-1, AKT, and ERK, and the increased cleavage of PARP and caspase 3/7, were the elucidated underlying molecular mechanisms of this phytochemical. The compound can be a promising candidate for future anticancer drug development.